(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2024)
This study aimed to identify the leadership patterns prevailing in the Ministry of media, and it is also aimed to know the level of morale spirit of employees in Ministry of media as well as to know the prevailing leadership patterns in level of morale spirit of employees in Ministry of media. The study used the descriptive methodology because it is suitable with the study issue through describing leadership patterns prevailing in Ministry of media. The study community represented in all those who are working in the Ministry of media from first rank up to the tenth rank that consisted of 322 employees where the questionnaire has been distributed to all study community individuals, about 242 questionnaires have been retrieved and (12) questionnaires have been removed due to its invalidity; therefore, the researcher has obtained (230) questionnaire valid for statistical analysis i.e. 71%. In order to fulfill the study objectives, the researcher has used the questionnaire as a tool for collecting study data that consisted of three parts (personal information, leadership patterns, the level of moral spirit). The study results revealed that the democratic pattern is prevailing in Ministry of media and following of corresponding and autocratic pattern by the officials in Ministry of media was not confirmed. It is clear from declination results that the independent variable (the democratic pattern) is the only independent variable that been inserted in declination equation for prediction by moral spirit position with employees of Ministry of media whereas the leadership pattern has been removed (Correspondence, autocratic) from the equation which stating that it doesn’t effect on morale spirit of employees in Ministry of media. In the light of these results the researcher recommended several recommendations the most important of which are: trying to do all that fostering the practice of Democratic leadership pattern in Ministry of media, awareness of leaders in Ministry of media not to be affected by workers’ desires, to encourage the leaders in Ministry of media to use justified evaluation among employees and to notify them by job justice and giving them money and morale incentives, guiding the leaders in Ministry of media to observe personnel’s capabilities when distributing the tasks among them, and directing leaders in Ministry of media to provide enough training opportunities to the workers.